Anaesthetic Management of a 1-Month-Old Puppy Undergoing Lateral Thoracotomy for Vascular Ring Anomaly Correction. (15th December 2011) - Martin Jurado, Olga; Mosing, Martina; Bettschart-Wolfensberger, Regula
Abstract : A 1-month-old male flat-coated retriever was anaesthetized for correction of oesophageal constriction caused by a vascular ring anomaly. Anaesthesia was uneventfully induced with intravenous fentanyl, diazepam, and propofol and maintained with isoflurane in oxygen and air. An intercostal block with bupivacaine and lidocaine was performed, and additional analgesia with an infusion of fentanyl was provided. Fluid therapy consisted in 5% glucose in lactated Ringer's solution and hetastarch 6%, which proved adequate to maintain normoglycemia and normovolemia. A lateral thoracotomy was performed, and the ligamentum arteriosum was ligated. Intraoperatively, heart rate (HR) varied between 120 and 180 beats min −1 without accompanying changes in blood pressure. No arrhythmias were observed or bleeding occurred. The dog recovered uneventfully. Postoperative analgesia consisted in fentanyl infusion adjusted to the patient's requirement and metamizol. This paper describes for the first time the use of balanced anaesthesia and multimodal analgesia in a paediatric dog undergoing thoracotomy.